THE SOUTH AFRICAN MILITARY IN TRANSITION: PART 2 – FROM STRATEGIC CULTURE TO STRATEGIC REALITY - Louw, Gerhard M; Esterhuyse, Abel (Scientia Militaria - South African Journal of Military Studies, 2014)
The analysis reported here focused on the dynamic interaction between a preferred strategic management model of the South African National Defence Force (SANDF) on the one hand, and the SANDF’s acquired strategic culture on the other. From a theoretical perspective, the analysis draws attention to the fact that the properties of institutional culture inform the extent to which an organisation (such as the SANDF) suffers the deleterious consequences of an inappropriate management model. The article therefore argues that the military’s lack of consensus on an appropriate political culture, the lack of a suitable social culture and the lack of an effective military culture have resulted in maintaining the continued viability of two discrete, concurrent strategic cultural paradigms in the SANDF: that of the defunct SADF[i] (initially dominant), and that of the obsolete MK[ii] (currently governing). The uneasy co-existence of these two paradigms, each with its own worldview and value system, has confounded the efforts of the SANDF to form an appropriate intended strategy and to realise military effectiveness in its execution. A dichotomous strategic culture has, in effect, reinforced the weaknesses of the SANDF’s strategic management model, impeded organisational responsiveness, maximised organisational entropy, and encouraged the defence force’s systemic decline – the latter, a fact that the Defence Review 2014 specifically acknowledges in the discussion of the review’s first milestone.[iii] This part mainly employs deductive reasoning and draws its conclusions from a focused literary review. [i] The South African Defence Force, prior to 27 April 1994. [ii] The abbreviation MK is used for Umkhonto we Sizwe (translated as “Spear of the Nation”), the armed force of the African National Congress (ANC) before 1994. It was the most important revolutionary armed force mobilised against the apartheid state. [iii] Republic of South Africa. “South African Defence Review 2014”. <http://www.sadefencereview2012.org/publications/publications.htm> Accessed on 21 October 2014.